2009
DOI: 10.1007/s10457-008-9196-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential of natural and improved fallow using indigenous trees to facilitate cacao replanting in Ghana

Abstract: Poor establishment, due to loss of soil fertility, weeds and lack of appropriate shade, is a major constraint to replanting cacao on previously used land. Spathodea campanulata, Newbouldia laevis and Ricinodendron heudelotii planted as monospecific improved fallow and Terminalia ivorensis, T. superba and Antiaris toxicaria planted as a multispecies improved fallow and a natural tree fallow were assessed for their potential to facilitate cacao replanting in a randomized complete block design experiment. Simpson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The leaf litter of the shade species had a much higher (P < 0.05) decay rate constant than the cocoa leaf litter treatment. Anim-Kwapong and Osei-Bonsu [75] found a similar high k d value of 2.51 × 10 −3 /day (recalculated from authors' half-life value of 9.22 for N. laevis) for N. laevis also collected from the same ER of Ghana. In respect of the decomposition rate of cocoa leaf litter in the present study, comparable leaf litter decay rates have been reported by Owusu-Sekyere et al [76] and for some forest tree species [77].…”
Section: Decay Constantmentioning
confidence: 57%
“…The leaf litter of the shade species had a much higher (P < 0.05) decay rate constant than the cocoa leaf litter treatment. Anim-Kwapong and Osei-Bonsu [75] found a similar high k d value of 2.51 × 10 −3 /day (recalculated from authors' half-life value of 9.22 for N. laevis) for N. laevis also collected from the same ER of Ghana. In respect of the decomposition rate of cocoa leaf litter in the present study, comparable leaf litter decay rates have been reported by Owusu-Sekyere et al [76] and for some forest tree species [77].…”
Section: Decay Constantmentioning
confidence: 57%
“…Additionally, pioneer species are better able to regenerate and survive in disturbed forests or forest-like systems, such as cocoa agroforests, than other species thus contributing to their abundance on cocoa farms. Indeed, most of the species among the ten most abundant species such as Milicia excelsa , Antiaris toxicaria , Alstonia boonei , Entandrophragma angolense , Ficus exasperata , Newbouldia laevis , Terminalia ivorensis , Terminalia superba and Spathodea campanulata have been cited as being compatible with cocoa by both farmers and scientists in Ghana [22; 40; 41]. That notwithstanding, the vegetation in the study area has been cited to be predominantly pioneer species due to significant deforestation that has taken place over the past five decades [23; 27].…”
Section: Discussionmentioning
confidence: 99%
“…They were valued by farmers for the quality of shade, soil fertility improvement and in the case of S. campanulata and R. heudelotii for their positive role in increasing soil moisture availability, especially in the dry season. The role of S. campanulata in increasing soil moisture has been previously recorded in Ghana (Anim-Kwapong and Osei-Bonsu 2009). Ricinodendron heudelotii is also known to root deeply, likely to reduce competition for water with cocoa, and because of the high market potential of its kernels, has been indentified as a promising tree species for domestication in West Africa (Tchoundjeu and Atangana 2007).…”
Section: Consensus On Compatibility Of Tree Species With Cocoamentioning
confidence: 95%